2005
DOI: 10.1016/j.jacc.2005.05.078
|View full text |Cite
|
Sign up to set email alerts
|

Gender-Related Differences in Rhythm Control Treatment in Persistent Atrial Fibrillation

Abstract: In female patients with persistent AF, a rhythm control approach leads to more cardiovascular morbidity and mortality. Because treatment strategy did not influence QoL in female patients, a rate control approach may be considered in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
119
3
9

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 209 publications
(139 citation statements)
references
References 32 publications
(37 reference statements)
8
119
3
9
Order By: Relevance
“…Previous studies of AF have shown varying results, with no differences in cardiovascular morbidity and mortality between females and males, 7,8 lower all-cause and cardiovascular mortality in females compared with males, 9 or higher mortality in females compared with males. 10 In our study, no difference was seen in cardiovascular death/SSE between females and males.…”
Section: Discussionmentioning
confidence: 88%
“…Previous studies of AF have shown varying results, with no differences in cardiovascular morbidity and mortality between females and males, 7,8 lower all-cause and cardiovascular mortality in females compared with males, 9 or higher mortality in females compared with males. 10 In our study, no difference was seen in cardiovascular death/SSE between females and males.…”
Section: Discussionmentioning
confidence: 88%
“…These findings are similar to previous reports. 38,39 Other factors that were shown to be associated with higher AF prevalence in this cohort such as age, BMI, and some comorbid conditions (lung disease and renal failure) are also known risk factors for AF. 37,40 -42 In addition, therapy with neurohormonal modulators (ACEI, ARB, and β-blockers) and statins were protective against AF in this patient population.…”
Section: Comparison To Previous Registries and Reportsmentioning
confidence: 83%
“…23 Furthermore, in this study, women had a significantly smaller stroke volume with a higher heart rate, a finding similar to that in previous studies, which also reported that women have a higher heart rate, longer duration of paroxysmal AF, and more frequent recurrence of arrhythmia cardioversion. 24,25 Another possible factors are increased LV and arterial stiffness in women. Recent studies have reported that women display increased arterial and ventricular stiffening and deranged ventricular-arterial coupling compared with men, particularly with aging.…”
Section: Discussionmentioning
confidence: 99%